2020
DOI: 10.1002/bjs.11603
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colorectal cancer associated with BRCA1 and/or BRCA2 mutation carriers: systematic review and meta-analysis

Abstract: Background Carriers of the BRCA1 and/or BRCA2 mutation incur a lifetime risk of up to 85 per cent for breast cancer, and between 20 and 40 per cent for ovarian cancer. Efforts to estimate the lifetime risk of developing colorectal cancer for BRCA mutation carriers have produced conflicting results. Consequently, there are no formal guidelines regarding the need for bowel screening for individuals with BRCA1 and/or BRCA2 mutations. This systematic review and meta‐analysis determined the risk of colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
2
29
1
Order By: Relevance
“…Two of the most frequently altered non-CRC hereditary cancer genes found in CRC patients are BRCA1 and BRCA2 ; however, the debate about whether those actually increase the risk of CRC is still ongoing [ 61 , 103 , 104 , 105 , 106 , 107 , 108 ]. A recent meta-analysis, together with familial/early onset CRC case-control data, indicate that BRCA1 and BRCA2 pathogenic variants do not increase the risk to CRC [ 109 , 110 ]. Contrarily, another meta-analysis suggests that pathogenic variants in BRCA1 increase CRC risk (OR = 1.56) but not in BRCA2 [ 111 ].…”
Section: Non-crc Hereditary Cancer Genesmentioning
confidence: 99%
“…Two of the most frequently altered non-CRC hereditary cancer genes found in CRC patients are BRCA1 and BRCA2 ; however, the debate about whether those actually increase the risk of CRC is still ongoing [ 61 , 103 , 104 , 105 , 106 , 107 , 108 ]. A recent meta-analysis, together with familial/early onset CRC case-control data, indicate that BRCA1 and BRCA2 pathogenic variants do not increase the risk to CRC [ 109 , 110 ]. Contrarily, another meta-analysis suggests that pathogenic variants in BRCA1 increase CRC risk (OR = 1.56) but not in BRCA2 [ 111 ].…”
Section: Non-crc Hereditary Cancer Genesmentioning
confidence: 99%
“…The cumulative breast cancer risk and ovarian cancer risk for mutation carriers are 5 times and 10-20 times higher than that for non-carriers (11), respectively. However, investigations on whether BRCA1/2 mutations increase lifetime risk of developing colorectal cancer have yielded conflicting results (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide [ 1 ], and evolves as a result of the accumulation of genetic and epigenetic events [ 2 ]. Data evaluated by the International Agency for Research on Cancer (IARC) indicated that about 1.8 million new cases of CRC were diagnosed and over 860,000 CRC patients died worldwide in 2018, which account for about 10% of all cancers and 9% of all cancer-related deaths, respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%